Stability-indicating TLC /Densitometric Method for Simultaneous Analysis of Febuxostat and Diclofenac Potassium in Bulk and Tablets - Mojeeb Gulzar Khan, Mohammad; Arun Shirkhedkar, Atul (Current Pharmaceutical Analysis, 2016)
Background: Febuxostat is xanthin oxidase inhibitor and Diclofenac Potassium is potent prostaglandin inhibitor. A fixed dose combination of febuxostat and diclofenac potassium is used for the treatment of gout. Objective: The presented work explains the development and validation of simple accurate TLC/Densitometric method for simultaneous estimation of Febuxostat (Feb) and Diclofenac potassium (Dic) in tablet formulation. Method: Precoated silica gel 60F254S TLC aluminium plates were employed as a stationary phase and the eluent cyclohexane- dichlorometane-ethyl acetate and formic acid (8/1/1/0.3, v/v/v/v) was uesd. Densitometric analysis of Feb and Dic was achieved at λmax 275 nm. The method validation was done by robustness, precision and accuracy. Stress degradation of Feb and Dic was carried out under different stress conditions like acid, base, oxidation, photo-degradation and dry heating. Result: This mobile phase system was observed to give compact spots for both Feb and Dic and the Rf values were 0.49±0.02 and 0.69±0.02 for Feb and Dic, respectively. Linear regression analysis data of Feb and Dic showed a good linear relationship in range of 200 –1200 ng/ spot and 500 - 3000 ng/spot, respectively. LOD and LOQ was found to be 15.39 and 46.63ng for Feb and 45.66 and 138.37ng for Dic. Conclusion: Statistical analysis confirmed that the developed method was repeatable and selective for the estimation of Feb and Dic in bulk, in formulation and in presence of their degradation products. As the method could efficiently separate the drug from its degradation products, it could be used as a stability- indicating method.
Keywords: HPTLC